The Dynamics of Toxic Relationships in Relation to Life Satisfaction and Self-Esteem Among Adult Women Following a Broken EngagementM. - Kurniawati, Ulfi Ledy; Ariyati, Ika; Sugiarto, Sugiarto (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Toxic relationships often have a profound psychological impact, especially on adult women who have experienced failed engagements. This condition can affect life satisfaction and self-esteem, and hinder the process of emotional recovery following a relationship. The purpose of this study was to understand the impact of toxic relationships on the life satisfaction and self-esteem of adult women who have experienced failed engagements. The approach used was phenomenology with in-depth interviews with three adult women who had gone through this experience. The results showed that toxic relationships negatively impacted life satisfaction and self-esteem as evidenced by emotional deterioration and barriers to self-development and decreased self-esteem caused by feelings of disrespect and loss of direction in life. The findings highlight the importance of understanding the emotional impact of toxic relationships and the need for social support to aid in the recovery process after relationship failure. This research may provide guidance for the development of interventions that support women's recovery after experiencing toxic relationships.